New taxa of Impatiens (Balsaminaceae) from Madagascar VI. Impatiens otto-eleonorae, a new species from Masoala Peninsula, and notes on the taxonomic relationships of Impatiens firmula and I. hildebrandtii - Fischer, Eberhard; Rahelivololona, Marie-Elisette (Phytotaxa, 2015)
The new species Impatiens otto-eleonorae Eb.Fischer & Rahelivolona from Masoala Peninsula is described. It is related to Impatiens hildebrandtii Baill. from Eastern Central Madagascar, but differs in the larger habit and flowers. The types of Impatiens firmula Baker and I. hildebrandtii are reinvestigated. Both taxa, previously considered to be identical, represent different species, and Impatiens hildebrandtii is reinstated here.